Integrating academic integrity into a masters preparation programme - Hyde, Christopher; Molyneux, Elizabeth; Anderson, Rheanne; Ketteringham, Matthew (KAZGUU University, Nazarbayev University, 2018)
In this session, the presenters will describe their approach to integrating academic integrity into a new Masters’ preparation programme at Nazarbayev University. One of the challenges of teaching and learning at an international university such as NU is the diversity of educational backgrounds among students and faculty.
Keywords: Academic Integrity; Nazarbayev University